Universal soldiers or parochial actors: understanding jihadists as products of their environments - Tankel, Stephen (Terrorism and political violence, 2019)
Why did the Islamic State of Iraq and al-Sham (ISIS) and Jabhat al-Nusra (JN)—two groups that shared similar ideological preferences and were both initially part of the Al Qaeda network—take different paths in the Syrian conflict? Part of the answer lies in the fact that JN is primarily a Syrian organization, whereas Iraqis lead ISIS. A jihadist group’s relationship to its country of origin and domicile (the two are not always the same) helps to explain that organization’s ideological preferences and alliance behavior. Yet no method of categorization based on jihadist-state relations exists. I fill this gap by theorizing an explanatory typology based on a jihadist group’s relationship with its country of origin and/or domicile. This typology consists of two tiers. The first classifies jihadist organizations based on whether they are nationally homogeneous or heterogeneous, and whether they are based in their country of origin, exile, or multiple locations. The second tier categorizes groups based on the nature of their engagement—collaborative, belligerent, or neutral—with a state. This new typology enables the generation of multiple hypotheses and has practical implications given that most U.S. counterterrorism efforts require cooperation from partner nations.